Sequence comparison of phoR, gyrB, groEL, and cheA genes as phylogenetic markers for distinguishing Bacillus amyloliquefaciens and B. subtilis and for identifying Bacillus strain B29 - Yu, C.; Jin, J.; Meng, L-Q.; Xia, H-H.; Yuan, H-F.; Wang, J.; Yu, D-S.; Zhao, X-Y.; Sha, C-Q. (Cellular and Molecular Biology, 2017)
Given the close genetic relationship between Bacillus amyloliquefaciens and B. subtilis, distinguishing the two solely based on their physiological and biochemical characteristics and 16S rRNA sequences is difficult. Molecular identification was used to discover suitable genes for distinguishing the two bacteria, and to identify the bio-controlling strain B29, due to molecular identification has been paid more and more attention. The similarity of four genes, cheA, gyrB, groEL and phoR, of the two species was compared by the software BLASTN and MAGA, and phylogenetic tree was constructed. The B29 strain was re-identified by using the screened genes. The similarities of the four genes, gyrB, groEL, cheA and phoR, of the two species were 93-95%, 82-84%, 76-78% and 76-77%, respectively. The homologies of the four genes of the strain B29 and the strains of B. amyloliquefaciens strains were more than 95%. We determined how well the phoR and cheA genes could be used to differentiate B. amyloliquefacien and B. subtilis. The previously isolated biological control strain B29, initially classified as B. subtilis, was re-classified as B. amyloliquefaciens. Our data indicate that other than the phoR gene, the cheA gene might be a useful phylogenetic marker for differentiating B. subtilis and B. amyloliquefaciens.